Die ontmoeting van wêrelde en die beginsel van sola Scriptura - Dreyer, Yolanda (HTS teologiese studies, 2015)
The meeting of worlds and the principle of sola Scriptura. Rather than function as a catalyst for unity, the Bible can be the cause of conflict among Christian believers. The Bible is also often the reason for strife, specifically in the Reformed tradition, even though Protestants uphold the creedal truism of sola Scriptura and though the authority of the Bible is seen as selfmandatory, transcending the normative power of ecclesiastical or confessional traditions. This article focuses on biblical interpretation as both a cause of disunity and a possible means to achieve greater unity. The point of departure is that biblical interpretation consists of a fusion of horizons; it is primarily about the fusion of two horizons, namely that of the Bible and that of the reader. However, both these horizons represent a great diversity of perspectives. A variety of readers interpret the Bible from diverse contexts. The Bible itself also communicates a diversity of ideas. Even the notion ‘Jesus Christ’ does not function as a unified or unifying concept. The article proposes that the idea of ‘Jesus’ cause’ (Sache Jesu) could provide continuity between the world of the reader and the world of a biblical passage.